Above, but close to two percent. Evidence on the ECB's inflation target using text mining - Johannes Zahner (Philipps-University Marburg, School of Business and Economics, 2020)
Due to its official mandate, the European Central Bank (ECB) is assumed to maximize an implied objective function that leads it to pursue inflation with a subordinate focus on supporting the general economic policy of the European Union. This objective is – by its very nature – difficult to quantify. My paper tries to decipher information regarding the ECB's objective through the use of text mining on all public speeches between 2002 and 2020. The estimation of a sentiment index through a 'bag-of-words'-approach yields the following results. First, the findings of my analysis suggest a concave objective regarding the inflation rate. The implied inflation target is best summarized as an inflation rate of 'above, but close to 2%'. Deviations from this target lead to a reduction in the sentiment of the institutions' communication. Second, my findings suggest a convex objective towards output growth and a linear objective towards the unemployment rate, with a preference for higher GDP growth and employent independently of the current level. Furthermore, the hierarchical order in the the European Central Bank (ECB)'s mandate does not always appear to be consistent with my findings. Deviations from its primary objective, the inflation rate, appear to be of no greater concern than deviations in its subordinate objective. Third, in periods of heightened uncertainty, there is an additional decrease in the sentiment of speech. Last, over the last two decades, speeches have become more pessimistic, even when controlling for macroeconomic conditions.
Keywords: E53; E58; E61; 330; Sentiment Analysis; ECB; Monetary Policy; Public Perception